Texting Language As A Digital Symbolic Current: Implications For Pragmatics And Intercultural Communication In The Digital Age. - Jimoh Junior Braimoh (The Journal of Studies in Language, Culture and Society, 2025)
This study investigates the influence of texting language on digital communication and its implications for pragmatics and intercultural communication. Utilizing a case study approach, the research examines the written work of final-year linguistics students at the University of Benin, Nigeria, to understand the extent to which short messaging service (SMS) abbreviations permeate academic writing. Building on the metaphor of texting language as a "common symbolic current" akin to the sardine metaphor, this paper explores how digital communication transcends cultural boundaries and creates new linguistic norms. The research is grounded in a comprehensive analysis of questionnaires, written assignments, and examination scripts from 62 students, highlighting the prevalence of SMS-related abbreviations in their written work. The findings reveal that while students frequently use texting abbreviations in informal contexts and notetaking, their usage in formal academic writing is more restrained (Braimoh, 2020). This indicates an awareness among students of the need to adapt their writing style to different contexts, thereby demonstrating a nuanced understanding of pragmatic competence in digital communication. Furthermore, the study discusses the broader implications of texting language on intercultural communication, emphasizing its role as a digital symbolic current that facilitates cross-cultural understanding. The paper concludes by suggesting that future research should explore the intersection of digital technologies, linguistic practices, and intercultural communication to further elucidate the impact of digital communication on language and culture.